Partnerships that support health systems resilience over time: a study of non-state, faith-based health providers in Africa - Maulit, Jolly Ann (Department of Public Health and Family Medicine, 2017)
Health systems resilience is an emerging issue in health policy and systems research, yet limited information exists on how resilient health systems are developed and the different elements that contribute to whole (national) health systems resilience. In this study, resilience is understood from the socio-ecological lens applicable for complex adaptive systems. Resilience therefore is not only the ability of a health system to address disturbances and restore its basic structures and functions, but also the ability of a health system to transform or re-organise in response to a disturbance if the current system is no longer tenable for the context. Along with the rise in the interest in health systems resilience is a renewed focus on partnership with nonstate providers (NSPs) to complement national health systems. The role of NSPs in supporting health systems resilience however has been largely unexplored. This study thus explores the topic of resilience with respect to health systems and focuses on a particular NSP type – namely, faith-based health providers (FBHPs). It describes four country cases of Ghana, Malawi, the Democratic Republic of Congo, and South Sudan - where FBHPs, though their inclusion in the health system and the activities they undertook, appear to have influenced the resilience of national health systems. FBHPs have played critical roles in strengthening health systems, which has been argued to be a key source of resilience. Their presence also diversified the actors in the health system, enabling them to step in as an alternative service provider when government services were unavailable. Historically, FBHPs appeared to be more flexible which allowed them to respond more quickly during times of crises. This flexibility in operations, coupled with their mission to serve marginalized populations, have supported the development of innovations for the poor, which in some instances have been adopted by national governments. As such, FBHPs have not only acted as buffers in times of shocks or stressors, but have also supported the transformation of national health systems for the better. Recent trends of closer integration with governments however are increasing the interdependencies between FBHPs and the public sector, which have potential to make health systems more vulnerable and less resilient.